2013
DOI: 10.1080/00221309.2013.783779
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric Differences in the Processing of Words Learned Early Versus Later in Childhood

Abstract: The research investigated whether there are hemispheric differences in processing for words acquired early in childhood (early AoA) and words acquired later in childhood (late AoA). We hypothesized that because of recent evidence suggesting that there is a right hemisphere dominance in early childhood, early AoA words would be represented in the right hemisphere, and late AoA words would be represented in the left hemisphere. This hypothesis differs from an early view that late AoA words would be represented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The results of numerous studies revealed that parental involvement had a potential to improve student achievement and behavior (Bourdieu and Passeron, 1990;De Graaf, 1986;Farkas et al, 1990). Also, Buchmann et al (2010) indicated that the benefits of parental involvement incorporated higher test scores and grades, better school attendance, greater completion percentage of homework, more positive attitudes and behavior, superior graduation rates and greater enrollment in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…The results of numerous studies revealed that parental involvement had a potential to improve student achievement and behavior (Bourdieu and Passeron, 1990;De Graaf, 1986;Farkas et al, 1990). Also, Buchmann et al (2010) indicated that the benefits of parental involvement incorporated higher test scores and grades, better school attendance, greater completion percentage of homework, more positive attitudes and behavior, superior graduation rates and greater enrollment in higher education.…”
Section: Discussionmentioning
confidence: 99%
“…They indicated their decision by pressing one of two keys on the computer keyboard (the "Y" key with the left forefinger, and the "B" key with the right forefinger; for half of the participants, the "B" indicated a word response, and for the other half this response was reversed). [AQ: 1] Following a similar procedure as Bowers et al (2013), each trial started with a central presentation of a white fixation cross for 400 ms on a black screen. After a 50-ms blank interval, the fixation cross was displayed in red for 50 ms. After another 50-ms blank interval, the cross reappeared in white for 400 ms.…”
Section: Methodsmentioning
confidence: 99%
“…Following a similar procedure as Bowers et al (2013), each trial started with a central presentation of a white fixation cross for 400 ms on a black screen. After a 50-ms blank interval, the fixation cross was displayed in red for 50 ms. After another 50-ms blank interval, the cross reappeared in white for 400 ms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurological aspect involves lateralization in the brain hemisphere, the biological schedule, the right brain hemisphere participation and the importance of accent (Bowers et al, 2013). As the child matures, brain lateralization takes place, with the left hemisphere controlling the logical, intellectual and analytical functions and the right hemisphere focusing on the social and emotional functions (Azmitia, 2007).…”
Section: Children Language Learningmentioning
confidence: 99%